(untitled) (AYUSHDHARA, 2020)
The plant Moorva is one of the Jwarahara plant explained in Ayurveda literatures. Brihatrayees explain extensively Moorva in Jwarahara formulations. Moorva is a controversial drug and currently many plants are being used in the name of Moorva. Controversy is probably due to scarcity and identical synonyms, which lead to substitution with locally available plants with structural similarity and same therapeutical actions. Efficacy of such plants as Jwarahara is evaluated. Charaka and Ashtanga Hridaya Samhita explain that Jwara causes decrease of strength and enthusiasm, reduces life span and immunity, and causes mental confusion involving body and mind. Harrison writes in Principle of Internal Medicine that antibacterial drugs are curative drugs in infectious diseases. Presently bacteria are developing resistance towards antibacterial agents and are responsible for worsening the life conditions in humans. Hence antibacterial screening of three species used as Moorva i.e. Clematis triloba, Maerua arenaria and Chonemorpha macrophylla was conducted. Materials and Methods: Antibacterial study of Methanol and aqueous extracts of above plants were done by Agar diffusion Method using Gram +ve strain (staphyllococi Aureus) and Gram –ve strain (Escheria Coli). Results: Overall results of study conclude that, Maerua arenaria with methanolic extract has inhibitory activity against Gram +ve strain at 1000µg. With the same extract it showed inhibitory activity against Gram –ve strain with 500µg and 1000µg concentrations. Aqueous extract of Maerua arenaria showed inhibitory activity against Gram +ve and Gram –ve strains at 100µg. Chonemorpha macrophylla showed inhibitory activity with methanolic extract on Gram –ve organism at 1000µg.